Pengaruh Shopping Lifestyle dan Hedonic Shopping Motivation terhadap Impulse Buying pada Shopee.Co.Id (Studi Kasus di Lingkungan Mahasiswa Kota Sukabumi) - Lathiyfah Shanti Purnamasari; Bambang Somantri; Viska Agustiani (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2021)
This study aims to determine the effect of: (1) Shopping Lifestyle on Impulse Buying, (2) Hedonic Shopping Motivation on Impulse Buying, (3) Shopping Lifestyle and Hedonic Shopping Motivation on Impulse Buying. The population and sample used in this study are 100 online shopee consumers who always do Impulse Buying. The data collection technique in this research is to use primary data sources from several questionnaires. The prerequisite tests for this study were the normality test, the multicollinearity test, and the hoeteroscedasticity test. The analytical method used is multiple linear regression analysis. The results of this study indicate that shopping lifestyle has a significant effect on impulse buying. Hedonic shopping motivation has not effect on impulse buying. Simultaneously, shopping lifestyle and hedonic shopping motivation have an effect on impulse buying.